The Method of Technology Evaluation Based on Improved Cost Approach - Aralova, N.I.; Kyiashko, O.Ye. (Science and Innovation, 2024)
An original method for evaluating title to intellectual property based on improved cost approach has been presented. An example of application to a specific task of evaluating a technology for manufacture of dual-use products has been given.